Recasting as a booster of Ag-Pd alloy cytotoxicity: induction of cell senescence prior to mass cell death - Čairović, Aleksandra D.; Stanimirović, Dragan M.; Krajnović, Tamara T.; Dojčinović, Biljana P.; Maksimović, Vesna M.; Cvijović-Alagić, Ivana Lj. (Archives of Biological Sciences, 2019)
Paper description: The toxicity of dental alloys in terms of continuous and prolonged exposure of cells in the oral cavity to certain materials is extensively documented. Our results showed that the cytotoxic effect of the Ag-Pd alloy against L929 cells was mediated by metal ion release in culture medium and provoked by recasting. Induction of senescence and cell death are basic mechanisms of alloy toxicity and are in correlation with casting number and endogenous ROS/RNS production. The data presented here underline the risk of Ag-Pd alloy reuse which compromises its biocompatibility, provoking complications observed in dental practice. Abstract: The biological quality and chemical composition of alloys used in dental practice changes during heat treatment. Often the residues of the previous cast are not disposed of but are reused and recycled until consumed. Thus, manufactured dental restorations have modified biological quality and chemical composition, and compromised biocompatibility. The aim of this study was to investigate the influence of repeated casting on the cytotoxicity of the silver-palladium (Ag-Pd) alloy. Our results showed that repeated casting of the Ag-Pd dental alloy affected its biocompatibility by promoting toxicity against transformed fibroblasts in a contact-independent manner. A strong decrease in cell proliferation, induction of senescence and massive cell death were observed in cultures exposed only to a medium previously incubated with dental alloy samples. The obtained data indicated that toxicity mediated by the accumulation of the Ag, Pd, Cu and Zn cations released from the Ag-Pd material was enhanced by recasting. The induction of cell senescence and subsequent apoptotic and necrotic death was accompanied by amplified intracellular production of reactive oxygen and nitrogen species, suggesting their involvement in the cell destruction process. Therefore, compromised biocompatibility after recasting with the Ag-Pd alloy can be the cause of serious local cell destruction, as observed in clinical practice. https://doi.org/10.2298/ABS190305017C Received: March 5, 2019; Revised: March 15, 2019; Accepted: March 21, 2019; Published online: March 25, 2019 How to cite this article: Čairović AD, Stanimirović DM, Krajnović TT, Dojčinović BP, Maksimović VM, Cvijović-Alagić ILj. Recasting as a booster of Ag-Pd alloy cytotoxicity: Induction of cell senescence prior to mass cell death. Arch Biol Sci. 2019;71(2):347-56.